Lexical semantics in the research on autism spectrum disorder - Hrycyna, Ewa (Papers in Linguistics, 2020)
The article deals with the problem of lexical semantics disorders in autism spectrum disorder (ASD). In the introduction, it is pointed out that semantics is analysed less frequently than pragmatics in ASD research. Having attempted to explain this disproportion, the author emphasises the need for further research into semantics in ASD. Then, the concepts of lexical ability, semantic ability, lexical competence and semantic competence are discussed refering it to people with ASD. The important role of the qualitative aspect in research is indicated. The article characterizes two perspectives of research on semantics in ASD – descriptive and explanatory. It is highlighted that people with ASD demonstrate considerably diverse language skills. Arguments are provided in favour of undertaking research into lexical semantics as beneficial for speech therapy theory and practice. It is postulated to take into account all linguistically and culturally relevant features of lexemes. The issues that should be addressed in future research are: multiple semantic variations in vocabulary, paradigmatic and syntagmatic relations, references to the ways words mean. The author hypothesizes which groups of lexemes may be especially interesting as material for research on lexical semantics in ASD. She also mentions the problem of applying linguistic theories (structural linguistics, cognitive linguistics) in speech therapy.